The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/es0305860
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Fate Model for Hexachlorocyclohexane in Tianjin, China

Abstract: A level III fugacity model was applied to characterize the fate of gamma-HCH in Tianjin, China, before the 1990s when the contamination reached its maximum at steady state. Geometric means were used as model inputs. The concentrations of gamma-HCH in air, surface water, soil, sediment, crops, and fish as well as transfer fluxes across the interface between the compartments were derived under the assumption of steady state. The calculated concentrations were validated by independent data collected from the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…Compared with other countries, the levels for most of the rivers in China were also found to have TCS concentrations in sediment more than 3 ng/g. When compared to the available reported concentrations in Chinese rivers, the differences between the PECs and MECs mostly fell within an acceptable range (less than a log-unit range) (Cao et al 2004;Liu et al 1999) (Table 4). The more measured concentrations from a river, the more representative the average value, especially for the large rivers.…”
Section: Prediction Of Tcs Concentrations In Each Basinmentioning
confidence: 90%
See 1 more Smart Citation
“…Compared with other countries, the levels for most of the rivers in China were also found to have TCS concentrations in sediment more than 3 ng/g. When compared to the available reported concentrations in Chinese rivers, the differences between the PECs and MECs mostly fell within an acceptable range (less than a log-unit range) (Cao et al 2004;Liu et al 1999) (Table 4). The more measured concentrations from a river, the more representative the average value, especially for the large rivers.…”
Section: Prediction Of Tcs Concentrations In Each Basinmentioning
confidence: 90%
“…Combining the chemical usage data, population, removal rate in WWTPs and a parameterized multimedia model describing the fate of chemicals, the chemical concentrations in the environment can be predicted, and it has been proved to be effective and accurate (Keller et al 2007;Price et al 2009Price et al , 2010aWhelan et al 2012;Zhang et al 2013). Multimedia fugacity models are well established, well documented and widely used for predicting the environmental fate of different chemicals at various scales (single river scale, regional scale and global scale) (Cao et al 2004;Mackay and Paterson 1991;Prevedouros et al 2004;Tan et al 2007;Tao et al 2003;Wang et al 2012). We have successfully modelled environmental fate for TCS in Dongjiang River basin ) and for seven steroids in whole China .…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of OCPs such as HCHs and dichlorodiphenyltrichloroethane (DDT) have also been historically produced at many chemical plants in this region. The wastewater from these factories was also discharged into adjacent rivers and has contributed large quantities of pesticides to the local loadings (Cao et al 2004). Although the production of PCP and these pesticides has been banned for decades, due to their high stability and resistance to microbial degradation, these pollutants can persist in aquatic sediments for decades and may still pose an ecological risk.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that a steady state could be reached with the constant input of chemicals, and that the modeling parameters that we collected within a year are reasonable. Based on the approaches of Mackay and Paterson 22 and Cao et al 40 a level III fugacity model was developed to describe the partitioning, reaction, and diffusive and non-diffusive transfer processes of TCS and TCC in the Dongjiang River basin as well as its different sections (upstream, midstream, downstream, delta). As the steady state fugacity model assumed, each study area in this study is completely mixed.…”
Section: Multimedia Modeling Methodologymentioning
confidence: 99%
“…23,45,46 In the analysis, probability distributions for input parameters were used to replace discrete values, by randomly selecting values from each input parameter distribution. 40 Through the Monte Carlo simulation method, the model ran 20 000 times and an output distribution of concentrations and transfer uxes in different environmental media were constructed. As the input parameters were assumed to have normal or log-normal distributions around the mean or point value (Fig.…”
Section: This Journal Is ª the Royal Society Of Chemistry 2013mentioning
confidence: 99%